New synonyms in the Australian micro-caddisfly fauna (Trichoptera: Hydroptilidae) - Wells, Alice (Zootaxa, 2012)
Discovery of new Trichoptera species in collections from mainland Australia is not unusual, and, currently a number of undescribed species are known in existing collections. However, few new species are likely to be found in Tasmania, the caddisfly fauna of which was collected intensively and formed the basis of a PhD study by Neboiss (1977). Subsequent to Neboiss’ work, several new species of Hydroptilidae — micro-caddisflies — were described from Tasmania by Wells (1999), and others recorded from the island (Neboiss 1981; Wells 1979a,b,c, 1980, 1981, 1985, 1997). Later, Neboiss (2003) revised the fauna, describing 17 new species collected over the years since his thesis work, none of them hydroptilids. More recently, Oláh and Johanson (2010) described two new micro-caddisfly species based on holotypes from Tasmania, for one of which a paratype is listed from SE Queensland; they also described three other new species from Queensland. Unfortunately, in preparing their paper, it seems that these authors failed to seek access to the extensive hydroptilid material in the collection of Museum Victoria, or the smaller collection in the Australian National Insect Collection, or to types of any closely similar Australian species. Nor, it appears, did they look closely at their specimens since at least four of these new names are found, on examination of the holotypes on which they are based, to be junior synonyms of established species. This short note presents the bases for decisions to suppress in synonymy the following four names of Olah and Johanson (2010): Helleythira hiana, Oxyethira elora, Orthotrichia lapka, and O. capa.